The effect of employment, economic growth, and investment on HDI: In provinces in Indonesia - Nur Feriyanto (Universitas Hayam Wuruk Perbanas, 2016)
This study aims to analyze the effect of Number of Working People (Employment), Economic Growth Rate (EGR), and Investment on Human Development Index (HDI) in Indonesia, partially and simultaneously. This study used investments consisting of Domestic Investment (DI) and Foreign Direct Investment (FDI). It used the method of analysis of panel data regression analysis with the data from thirty-three provinces in Indonesia from 2006 to 2013. The results indicate that the employment variables have positive and significant impact to HDI in Indonesia. It shows that EGR does not affect HDI in Indonesia. However, Domestic and foreign direct investments partially have positive and significant effect on HDI in Indonesia. Simultaneously, the variables employment, EGR, domestic and foreign direct investments have a significant effect on the HDI in Indonesia.